A Rapid, Low‐Cost, and Scalable Technique for Printing State‐of‐the‐Art Organic Field‐Effect Transistors - Temiño, Inés; Del Pozo, Freddy G.; Ajayakumar, M. R.; Galindo, Sergi; Puigdollers, Joaquim; Mas‐Torrent, Marta (Advanced materials technologies, 2016)
In the last few years exciting advances have been achieved in developing printing techniques for organic semiconductors, and impressive mobility values have been reported for the resulting organic field‐effect transistors (OFETs). However, not all these techniques are scalable and some of them require additional crystallization steps. This study reports on the fabrication of OFETs employing blends of four benchmark organic semiconductors with polystyrene and demonstrates that applying the same formulation and experimental conditions for printing them, highly reproducible and uniform crystalline films exhibiting high OFET performance are successfully achieved. It is noted that the mobility values achieved here are not the highest reported for the studied materials; however, they are state‐of‐the‐art values and could be regarded as exceptional considering the low cost and fast speed of the fabrication process involved here. Highly reproducible and uniform crystalline films of four benchmark organic semiconductors with polystyrene are successfully printed by bar‐assisted meniscus shearing applying the same formulation and experimental conditions. The performance of the resulting organic field‐effect transistors can be regarded as exceptional considering the low‐cost and fast speed of the fabrication process involved.